Ijtihad Maqashid Sharia in the Thought of Asy-Syatibi and Muhammad At-Tahir Ibn Ashur - Tabrozi, Dhika (UIN Sunan Kalijaga Yogyakarta, 2025)
The study of ijtihad in maqashid shariah within the thoughts of asy-Syatibi and Ibn Ashur contains a rational intellectual substance. However, previous studies have not fully explored asy-Syatibi and Ibn Ashur’s perspectives in elaborating the methodological foundations of maqashid shariah. This study employs a qualitative approach through a literature review on the thoughts of asy-Syatibi and Ibn Ashur regarding maqashid shariah, utilizing content analysis as its research method. The primary data is sourced from al-Muwafaqat and Maqashid al-Shariah al-Islamiyyah. Meanwhile, secondary data is derived from texts that correlate with the maqashid perspectives of both scholars. The data is then analyzed to understand the epistemological framework of asy-Syatibi and Ibn Ashur’s ijtihad. The findings of this study reveal that Asy-Syatibi argues that the implementation of shariah for mukallaf aims to achieve maslahah in relation to religious well-being and sustenance in worldly life. Asy-Syatibi mapped the core principles of the maslahah framework onto the five primary necessities (ad-dharuriyyat al-khams). Flexibility in worship is positioned as a secondary need, while the cultivation of akhlaq al-karimah serves as a complementary element in achieving the objectives of maqashid shariah. Meanwhile, Ibn Ashur’s concept of maqashid shariah distinguishes between maslahah that is general and maslahah that is specific. Maslahah ‘ammah presents a framework that categorizes needs into primary, secondary, and tertiary levels. Meanwhile, maslahah khassah focuses on specific benefits for individuals, encompassing worship (ibadah), transactions (mu‘amalat), family law, and criminal law. The concept of ibadah aims to purify both the soul and body, while mu‘amalat seeks to establish justice in individual rights within social contracts. Family law serves to protect the rights of the husband, wife, and children, whereas criminal law is designed to uphold justice. The concept of maqashid shariah proposed by asy-Syatibi and Ibn Ashur serves as a bridge and provides solutions to contemporary challenges related to modern issues and Islamic law. Kajian ijtihad maqashid syariah dalam pemikiran asy-Syatibi dan Ibnu Asyur memuat substansi pemikiran yang rasional. Namun, penelitian terdahulu belum sepenuhnya membahas pemikiran asy-Syatibi dan Ibnu Asyur dalam mengelaborasi landasan metodologis maqashid syariah. Penelitian ini menggunakan pendekatan kualitatif berupa studi pustaka terkait pemikiran maqashid syariah asy-Syatibi dan Ibnu Asyur dan metode analisis konten. Data primer bersumber dari kitab al-Muwafaqat dan Maqashid Syariah al-Islamiyyah. Sedangkan data sekunder lainnya bersumber dari teks yang memiliki korelasi dalam maqashid kedua tokoh tersebut. Data kemudian dianalisis untuk memahami kerangka epistemologis dari pemikiran asy-Syatibi dan Ibnu Asyur dalam berijtihad. Hasil kajian ini menemukan bahwa asy-Syatibi berpendapat pemberian syariat kepada mukalaf bertujuan untuk mewujudkan maslahah dirinya pada kemaslahatan agama dan keberlangsungan hidupnya di dunia. Asy-Syatibi memetakan pokok pemikiran maslahahnya pada lima kebutuhan primer (ad-dharuriyyat al-khams). Keringanan dalam beribadah diposisikan sebagai kebutuhan sekunder dan tercipatnya akhlaqul-karimah sebagai penyempurna maqashid syariah. Sedangkan gagasan maqashid syariah oleh Ibnu Asyur menunjukkan adanya maslahah yang bersifat umum dan bersifat khusus. Maslahah ‘ammah menawarkan konsep kebutuhan primer, sekunder, dan tersier. Maslahah khassah menawarkan konsep kemaslahatan secara khusus bagi individu yang terdiri atas ibadah, muamalat, hukum keluarga, dan hukum pidana. Konsepsi ibadah bertujuan untuk membersihkan jiwa dan raga manusia, muamalat bertujuan untuk menciptakan keadilan pada hak-hak individu dalam kontrak sosial, hukum keluarga melindungi hak suami, istri serta anak, dan hukum pidana bertujuan untuk menegakkan keadilan. Gagasan maqashid syariah yang diutarakan oleh asy-Syatibi dan Ibnu Asyur mampu menjembatani dan menjawab tantangan zaman yang berkaitan dengan problem modern dan hukum Islam.